Physical and chemical audits and comparative analyses of scrap remelting technology indicators for high-alloyed steel with special purposes using the duplex-slag process and the resource-saving mono-slag process - Proidak , Yu.S.; Gorobets , A.P.; Zhadanos , O.V.; Kamkina , L.V.; Yaroshenko , Ya.O. (Theory and Practice of Metallurgy, 2025)
The goal. The research purpose is a physicochemical audit and comparative analysis of the indicators of the technologies for remelting scrap of high-alloy special-purpose steels using a two-slag process and a resource-efficient single-slag process to create an innovative technology for the electric steelmaking process. Methodology. The research used miscellaneous methods and modern equipment for studying the physical chemistry of metallurgical processes, including optical metallography methods on the “Neophot-24” installation, to assess the microstructure of the metal and the mineralogical composition of the slags. Experimental and industrial smelting was carried out to determine the balance of alloying elements by certified chemical and spectral analysis of the metal and slag. Results and scientific novelty. To ensure the rational composition of the slag of reduced basicity during melting, a mixture with the following composition was synthesized from oxides classified as "chemically pure": 50%СаО-35%SiO2-5%Al2O3-5%MgO-5%FeO. This allows for the reduction of the loss of alloying elements and increases the efficiency of remelting. According to the results of the analysis conducted by the requirements of DSTU 8966:2019 regarding the contamination of the metal with non-metallic inclusions and their crystalline and chemical composition, it was found that the vast majority of inclusions are represented by silicates with a size of 7-10 μm. These indicators depend on the size and conditions of crystallization of the ingot. Changes in the content of alloying elements due to the remelting process were analyzed. It was confirmed that the losses of expensive alloying elements (Cr, Mo, W, V) depend not only on their chemical affinity for oxygen but also on the formation of compounds of the type СаО*МеО in the slag, where МеО oxide has an acidic nature of interaction. New knowledge has been obtained regarding the physical properties and phase composition of lime-iron slag of the CrO-FeO-SiO2-(Ме)O system where Me-Mn, Cr, V, Mo. The obtained scientific results significantly complement the research of domestic and foreign scientists due to the novelty of the approach and practical orientation to the needs of specific industries. Practical value. The developed technological solutions for predicting the optimal composition of the metal dump for metal scraps of alloyed special-purpose steels will increase the technical and economic performance of steelmaking in electric furnaces and promote the reuse of valuable materials. This is important in the context of the constant increase in the cost of raw materials and efforts aimed at reducing the impact on the environment, as well as on the sustainable development of Ukraine (solving environmental problems, reducing greenhouse gas emissions, reducing the consumption of ferroalloys, etc.).